Attitudes Toward the Utes Nickname and Logo - Yeo, Sara (Undergraduate Research Journal; 2017, 2017)
Sports teams with American Indian (AI) nicknames and logos have encountered controversy over the last 30 years, experiencing backlash attributed to their negative cultural and societal effects. Discussion of the acceptability of these symbols and images has been particularly persistent at schools that use AI nicknames or logos. At the University of Utah (UofU), rhetorical analysis of the use of the Utes nickname and logo have been conducted. The present work adds to existing scholarship by employing quantitative data to examine people’s attitudes toward the Utes nickname and logo. Specifically, we conduct a survey to assess individual attitudes on campus toward an array of AI cultural issues and concerns. As many concerns about the use of AI imagery and culture arise in the context of athletics, we also examined perceptions toward AI culture in these settings. The implications of these findings are discussed.
Keywords: american indian nicknames, american indian logos, native american studies, native american mascots